2018
DOI: 10.3389/fncel.2018.00325
|View full text |Cite
|
Sign up to set email alerts
|

The Role of KLF4 in Alzheimer’s Disease

Abstract: Krüppel-like factor 4 (KLF4), a member of the family of zinc-finger transcription factors, is widely expressed in range of tissues that play multiple functions. Emerging evidence suggest KLF4’s critical regulatory effect on the neurophysiological and neuropathological processes of Alzheimer’s disease (AD), indicating that KLF4 might be a potential therapeutic target of neurodegenerative diseases. In this review, we will summarize relevant studies and illuminate the regulatory role of KLF4 in the neuroinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 108 publications
(124 reference statements)
0
30
0
Order By: Relevance
“…Analysis of transcription factors identified KLF4 as a common regulator in AD, VaD and FTD. The role of KLF4 as potential therapeutic target in AD has been proposed [54]. Silencing of KLF4 attenuated the release of proinflammatory cytokines caused by accumulation of Aβ42 oligomers in a cellular model of AD [55].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of transcription factors identified KLF4 as a common regulator in AD, VaD and FTD. The role of KLF4 as potential therapeutic target in AD has been proposed [54]. Silencing of KLF4 attenuated the release of proinflammatory cytokines caused by accumulation of Aβ42 oligomers in a cellular model of AD [55].…”
Section: Discussionmentioning
confidence: 99%
“…KLF4, a transcription factor and cell-cycle suppressor, has been shown to be implicated in various human diseases ( Wang et al, 2016 , 2018 ; Xu et al, 2020 ). In addition, KLF4 was uncovered to be relevant to the pathogenesis of Alzheimer’s disease ( Cheng et al, 2018 ). Previous evidence also reported that KLF4 silencing protected against MPP + -evoked cytotoxicity in PD ( Chen et al, 2013 ; Kong et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of KLF2 and KLF4, which negatively regulate proliferation, inflammation, and angiogenesis, upregulate eNOS, and are sharply downregulated at sites of low and disturbed shear stress, were not different in collaterals versus DMAs. Interestingly, PrC promote Klf2, Klf4 , and eNOS expression [35,36,37,44,69,70].…”
Section: Discussionmentioning
confidence: 99%